Factors Affecting Tax Collection in Luang Prabang Province - LUANGLATH, Thipphaphone; SOMSAMONE, Vilayphone; XIONGTOUA, Tongvang (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study is a quantitative research that examines the relationship between international trade and tax revenue in Luang Prabang Province, Lao PDR. The study used secondary annual data from 2011 to 2024, collected from relevant government agencies, including provincial tax and trade authorities. The research aimed to analyze the short-run effects of exports and imports on tax revenue; To examine the long-run relationship between trade variables and tax revenue; and to assess the speed of adjustment toward long-run equilibrium following short-term economic shocks. To achieve these objectives, the study employs econometric techniques, including unit root tests, cointegration analysis, and an error correction model (ECM). The results show that imports have a significant positive effect on tax revenue in the short run, while exports do not exhibit a significant short-run impact. In the long run, exports are found to have a positive and significant relationship with tax revenue, whereas imports do not show a significant long-run effect. In addition, the ECM results indicate a slow adjustment toward long-run equilibrium. Overall, the findings suggest that imports play an important role in short-term revenue generation, while exports are a key driver of long-term tax revenue growth. These results provide useful implications for policymakers in designing trade and fiscal policies to support sustainable economic development in Luang Prabang Province.